Board games for teaching English prosody to advanced EFL learners - Kacper Łodzikowski; Mateusz Jekiel (Oxford University Press, 2019)
This exploratory study fills the gap in research on using print board games to teach English prosody to advanced EFL learners at university level. We developed three in-class print-and-play board games that accompanied three prosody-related topics in a course in English phonetics and phonology at a Polish university. For those topics, compared to topics without any board games, learners reported higher in-class engagement and obtained higher post-class quiz scores. At the end of the course, learners rated board games as equally or more useful than some of the other teaching aids. While traditional printed worksheets were still rated as the most useful teaching aid, learners expressed their preference for using extra classroom time for playing board games instead of completing extra worksheet exercises. We hope these promising results encourage teachers to experiment with implementing these and other board games in their advanced curricula.